Perkembangan Ekonomi di Indonesia Melalui Kebijakan Moneter Syariah - Kaila Zulfa Khoirurrizki; Putri Karina Sabila; Zakia Khoirunisa; M. Taufiq Abadi (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
The Islamic economic system can contribute to world economic growth, including in Indonesia. The purpose of this article is to analyze monetary policy in Indonesia from an Islamic economics perspective. This research examines monetary policy instruments, namely open market operations, with the aim of encouraging economic growth and stabilizing inflation. The method used is a literature review in three main journals and several articles in national and international journals about Islamic finance. The main focus of this research is monetary policy in Indonesia, which has a significant impact on the country's economic growth. The Islamic economic system can contribute to world economic growth, especially in Indonesia.